(untitled) (Journal of the College of Basic Education, 2022)
Praise be to God, Lord of the Worlds, and prayers and peace be upon the master of eloquence and the imam of the eloquent, Muhammad, may God bless him and grant him peace, and upon his pure and chaste family, and those who follow them in goodness until the Day of Judgment.The focus of the research revolves around (the mechanisms of graphic formation of irony in the Souri Diwan) as a critical term that works in the field of poetry on an influential scale, and is highly manifested in procedural use; As the image embodied in the space of the poem takes the emotional and emotional flow; This is because of the tools it possesses that highlight the literary work, and the elements that awaken the souls and stir up the passion for an emotional experience, and thus they are fixed in poetry; Because it expresses the poet’s psyche and a container for his feelings and thoughts, so it is necessary to reveal a deeper meaning than the apparent meaning (). That is why the poet began to use pictorial means such as simile, metaphor, and metaphor to help him in the process of poetic formation by creating models and forming words that go beyond the familiar and the usual. Souri relied in his poetry on forming different methods of graphic images, with the aim of ridicule. The subject of the research was (mechanisms of graphic formation of irony in the Suri Diwan).The research was divided into:First: the sarcastic metaphor.Second: borrowing.Third: the metaphor.In conclusion, I ask the Almighty God to provide us with His help and success, for He is the best of the Lord and the best of the Helper.